Aristolochia quiricoana (Aristolochiaceae), a new species from southern Costa Rica - Jiménez Vargas, José Esteban (2021)
Background and Aims: Aristolochia is the largest genus in Aristolochiaceae and is widely distributed in the world. A recent synopsis of Aristolochia in Costa Rica recognized 19 species; nevertheless, recent botanical exploration in southwestern Costa Rica has revealed yet another new species of this genus. Methods: The new species resulted from fieldwork in Buenos Aires, Puntarenas Province. Specimens from several herbaria were examined, as well as the type material of the most morphologically similar species. Comments about its distribution, habitat, phenology, conservation status and morphological distinction from related species are provided. Key results: Aristolochia quiricoana, a member of Aristolochia series Thyrsicae, is described and illustrated from the southern Pacific region of Costa Rica, where it is apparently endemic. It is similar to A. ornithorhyncha, from which it is distinguished by its shorter pedicels, wider, oblong perigone limbs with a shorter appendix, and a different floral color pattern. Conclusions: The new taxon described here represents the 22nd species documented in Aristolochia series Thyrsicae, as well as the 20th species of the genus from Costa Rica.